Brexpiprazole, a Serotonin-Dopamine Activity Modulator, Can Sensitize Glioma Stem Cells to Osimertinib, a Third-Generation EGFR-TKI, via Survivin Reduction - Suzuki, Shuhei (Cancers (Basel), 2019)
Glioblastoma is a primary brain tumor associated with a poor prognosis due to its high chemoresistance capacity. Cancer stem cells (CSCs) are one of the mechanisms of chemoresistance. Although therapy targeting CSCs is promising, strategies targeting CSCs remain unsuccessful. Abnormal activation of epidermal growth factor receptors (EGFRs) due to amplification, mutation, or both of the EGFR gene is common in glioblastomas. However, glioblastomas are resistant to EGFR tyrosine kinase inhibitors (EGFR-TKIs), and overcoming resistance is essential. Brexpiprazole is a new, safe serotonin-dopamine activity modulator used for schizophrenia and depression that was recently reported to have anti-CSC activity and function as a chemosensitizer. Here, we examined its chemosensitization effects on osimertinib, a third-generation EGFR-TKI with an excellent safety profile, in glioma stem cells (GSCs), which are CSCs of glioblastoma. Brexpiprazole treatment sensitized GSCs to osimertinib and reduced the expression of survivin, an antiapoptotic factor, and the pharmacological and genetic inhibition of survivin mimicked the effects of brexpiprazole. Moreover, co-treatment of brexpiprazole and osimertinib suppressed tumor growth more efficiently than either drug alone without notable toxicity in vivo. This suggests that the combination of brexpiprazole and osimertinib is a potential therapeutic strategy for glioblastoma by chemosensitizing GSCs through the downregulation of survivin expression.